Subcontractor selection practices in international construction projects - Ulubeyli, Serdar; Manisali, Ekrem; Kazaz, Aynur (Journal of Civil Engineering and Management, 2010)
This paper presents a study of subcontractor selection practices of Turkish contractors in international projects. The results highlight the current subcontracting practices of main contracting firms that have resulted in a long‐lasting market share abroad. Toward this aim, a detailed questionnaire was administered to 96 construction companies. Turkish and host countries’ subcontractors were shown to be frequently employed in international projects. However, subcontracting firms from other countries were found to not be used. Main contracting companies generally select subcontractors in the periods after the main tender or after the project's start. Although many of them often work with previously known subcontracting companies and do not take into account the lowest bid price as the primary criterion, systematic processes or models are not used to select the best subcontractor. Most importantly, main contractors not only use subcontractors but also carry out activities using their in‐house resources. Hence, this study will not only be a step for further works that can be performed by potential researchers who may find interesting similarities or differences between their countries and Turkey, but also assist contractors who plan to strengthen their positions and to increase work opportunities in the international market.First Publish Online: 15 Oct 2010